Retrospective Analysis of the Effectiveness of a Reduced Dose of Idarucizumab in Dabigatran Reversal - Stone, Louisa; Merriman, Eileen; Hanna, Merit; Royle, Gordon; Chan, Henry (Thrombosis and Haemostasis, 2022)
Background The recommended dose of idarucizumab, the specific reversal agent for dabigatran etexilate, is 5 g. However, published data showed biochemical reversal after an initial 2.5 g dose.Objectives This study aims to retrospectively compare the clinical effectiveness of 2.5 and 5 g doses of idarucizumab used in dabigatran reversal in three hospitals in Auckland, New Zealand.Methods All patients receiving idarucizumab for dabigatran reversal between April 1, 2016 and December 31, 2018 were included. The primary outcome was the likelihood of receiving a second dose of idarucizumab during the same admission. Secondary outcomes included normalization of coagulation profiles, and 30-day thrombotic, bleeding, and mortality rates.Results Of 329 patients included, 206 received an initial 2.5 g dose and 123 received a 5 g dose. The median age was 78 years and median creatinine clearance was 50 mL/min. Most patients (62.6%) required idarucizumab for an urgent procedure, while 37.4% presented with bleeding. A 2.5 g dose was not associated with an increased rate of receiving a second dose (odds ratio [OR]: 0.686, 95% confidence interval [CI]: 0.225–2.090). A similar proportion of patients in each group achieved a normal activated partial thromboplastin time (73.8 vs. 80.0%, p = 0.464) and dilute thrombin clotting time (95.9 vs. 91.4%, p = 0.379) following idarucizumab infusion. There was no increase in the rate of death (OR: 0.602, 95% CI: 0.292–1.239), thrombosis (OR: 0.386, 95% CI: 0.107–1.396), or bleeding (OR: 0.96, 95% CI: 0.27–3.33) in the 2.5 g dose group compared with the 5 g dose group.Conclusion An initial 2.5 g dose of idarucizumab appears effective for dabigatran reversal in the real-world setting.
Keywords: dabigatran; idarucizumab; anticoagulant; bleeding; thrombosis